Pelatihan Pembuatan Lilin Aromaterapi Berbahan Minyak Atsiri Papua Bagi Pengusaha Muda di Rumah BUMN Jayapura - Gunaedi, Tri; Zebua, Lisye Iriana; Panjaitan, Eunike Marito (JURNAL PENGABDIAN PAPUA, 2025)
The natural resource processing industry in Jayapura has begun to show results, especially in the form of local food and medicine products. Local product-based industrial products that have not yet reached industry players in Jayapura, such as aromatherapy candle products with essential oil extracts from plants in Papua. Aromatherapy candles are generally used to provide aromatherapy where the aroma can refresh the body and some can also repel mosquitoes, depending on the essential oils mixed into the candle making ingredients. Making aromatherapy candles is not difficult, does not take long, the raw materials are cheap and have a high selling value compared to the price of the raw materials. Based on this, it is very potential to be used as a commodity for industry players who are just starting their business. The implementation of the training in collaboration with the Jayapura BUMN House fostered by BRI Jayapura Branch, so that for the formation of new entrepreneurs who want to develop it, it has been prepared with its business funders, it is hoped that they will be able to become Micro, Small and Medium Enterprises (MSMEs), who are reliable in the aromatherapy candle industry made from essential oils from Jayapura and its surroundings. The training was conducted by providing material that was carried out with demonstrations by students who had been drilled by instructors, followed by a trial of making aromatherapy candles carried out by training participants. Evaluation was carried out by organoleptic testing of the level of preference for the resulting product in terms of aroma, texture, color, appearance using a Likert scale with a scale of 5, namely (1) Dislike, (2) Less like (3), Somewhat like, (4) Like, and Really like (5). Training participants were able to make aromatherapy candles well and liked the aromatherapy candle products from the training results.